Development of E-modules as Learning Modules in Vocational High Schools: Pengembangan E-modul Sebagai Modul Pembelajaran di Sekolah Menegah Kejuruan - Siti Uswatun Khasanah; Rahmania Sri Untari (Academia Open, 2022)
A person's dependence on technology that can occur outside and within the scope of the school, students are required to be smart in filtering information obtained from cyberspace. The first objective of this research is to produce a product in the form of an e-module as a learning module in SMK and the second objective is to determine the development and feasibility of the e-module that has been developed. The development model used is the ADDIE model which consists of five stages of analysis, design, development, implementation and evaluation. The results of the analysis carried out by the researcher is that there are problems in the learning process, namely when learning the teacher distributes material in the form of different media. This becomes a problem for students and teachers in the learning process. Like opening from one application to another, it makes students feel difficult when learning takes place, so learning becomes less effective. Based on the results of the development, it was found that the development of e-modules as learning modules in Vocational High Schools was recognized for its feasibility as a learning medium. The results of the media validator get a percentage of 88% with a very decent category, the results of material expert validation get a percentage of 80% with a decent category and student responses get a score of 88% with a very decent category. Highlights: Growing dependence on technology calls for improved information filtering skills. E-module development using the ADDIE model ensures a systematic approach. High feasibility of the e-module is supported by media and material expert validation, as well as positive student responses. Keywords: dependence on technology, e-module, learning module, ADDIE model, feasibility.